Respuesta :

xy=11
x+y=-26


x+y=-26
minus x both sides
y=-26-x

sub for y
x(-26-x)=11
-26x-x^2=11
add 26x+x^2 both sides
x^2+26x+11=0

ax^2+bx+c=0
x=[tex] \frac{-b+/- \sqrt{b^{2}-4ac} }{2a} [/tex]


a=1
b=26
c=11

x=[tex] \frac{-26+/-\sqrt{26^{2}-4(1)(11)} }{2(1)} [/tex]
x=[tex] \frac{-26+/-\sqrt{676-44} }{2} [/tex]
x=[tex] \frac{-26+/-\sqrt{632} }{2} [/tex]
x=[tex] \frac{-26+/-2\sqrt{158} }{2} [/tex]
x=[tex] -13+/-\sqrt{158} [/tex]

x=[tex] -13+\sqrt{158} [/tex] or [tex] -13-\sqrt{158} [/tex]

aprox

x=-0.420195 or -25.5698

those are the numbers